Green Communication Schemes of Heterogeneous Network-Based Electricity Emergency Communication Scene - Chunxin Wang; Xin Li; Xiaoxiang Wang; Zhaofeng Li; Lei Yan (Dianxin kexue)
Green communication is a new communication concept of promoting energy conservation and emission reduction as well as improving energy efficiency. With the growing energy shortage and environmental pollution, green communications has become the research hotspot of all the industry. The energy-saving potential of heterogeneous network-based electricity emergency communication system was analyzed and green communication schemes in network and device level were proposed. The objective is to save energy under the premise of ensuring the communication quality and consequently respond to the green communication needs.